STUNTING: EARLY DETECTION WITH ANTHROPOMETRIC MEASUREMENTS AND MANAGEMENT - Ayukarningsih, Yoke; Sa’adah, Hindun; Alif Kusmayadi, Mulya; Ramadhan, M.Zidan (Journal of Health and Dental Sciences, 2024)
Stunting is a condition of short stature in which the length or height of the body is not appropriate for the age when compared to the growth curve. Stunting is also known as a condition of failed growth in children (body and brain growth) caused by long-term malnutrition related to low socioeconomic status, poor maternal nutrition and health, history of recurrent illness, and inappropriate infant and child feeding practices. One way to detect initial stunting is through anthropometric measurements. Early detection prevents stunting with periodic measurements of weight and height according to age, which can help prevent and manage stunting. This research method is a literature review. Literature searches use online databases such as Google Scholar, including PubMed, DOAJ, and GARUDA, for articles published in the last ten years. Keywords related to the theme are applied during the article search process. A total of 14 articles or journals were selected as study materials. The results of the literature review explain the epidemiology, aetiology, risk factors, anthropometric measurements, and prevention of stunting in children. In conclusion, early detection through anthropometric measurements can prevent stunting and ensure more optimal management. DOI : 10.54052/jhds.v4n1.p91-104